Inflammatory and post-inflammatory lesions in the sacroiliac joints and lumbar spine according to magnetic resonance imaging in patients with early axial spondyloarthritis - D. G. Rumyantseva; Sh. Erdes; A. V. Smirnov (Научно-практическая ревматология)
Investigation of the evolution of early axial spondylitis (axSP) is now of great importance especially before the appearance of reliable radiological signs of ankylosing spondylitis (AS). Of particular interest is the assessment of inflammatory and post-inflammatory changes in the sacroiliac joints (SJ) and in the spine using magnetic resonance imaging (MRI). The aim of the study was to analyze inflammatory foci in bone according to MRI in the area of SJ and lumbar spine (LS) in patients with early axSP. Material and methods. The study involved the patients of the Moscow cohort CORSAIR (Early Spondyloarthritis Cohort), which was formed in V.A. Nasonova Research Institute of Rheumatology. Low field MRI of SJ and LS was carried out in all patients at inclusion in the study in the T1 and STIR modes. Results and discussion. SJ MRI most often (34.1%) revealed combined foci of inflammation (active and chronic sacroiliitis – SI), 32.9% of patients showed signs of only chronic, rarely – only active SI (19.5%). In a few cases, MRI showed inflammatory changes in LS, which were regarded as active and chronic spondylitis. In patients with a disease duration of up to 1 year, signs of active SI were more common according to MRI than in patients with a longer duration of the disease (30.0 and 14.4%, respectively; p<0.05). All active foci of inflammation (with or without signs of chronic SI) were significantly more frequently detected in patients with AS than in non-radiological axSP (NR-axSP; 61.6% and 44.2%, respectively; p<0.05). The overall incidence of chronic spondylitis (in combination with or without active spondylitis) in patients with AS was higher than in NR-axSP(13.9% and 5.8%, respectively; p<0.05).Conclusion. Patients with AS more often have active lesions at MRI of SJ and chronic ones at MRI of LS than patients with NR-axSP